The extent of Using Eduwave by North-eastern Badia Directorate of Education Principals From the point of view of principals - Aledamat, Mohammad Hamed (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the extent to which educational supervisors in the North-Eastern Badia region have technical competencies in the light of quality standards from the point of view of school principals, and identify the impact of both sex, educational qualification and years of experience in this study. A questionnaire was distributed to all study population (154) principals and principals of the schools of the North-Eastern Badia Directorate. The results showed that the extent of the educational supervisors in the North-East Badia region of technical competencies in the light of quality standards School administrators rated the tool as a whole; got an average (3.57 out of 5) with a grade of (average), and at the pivot level; the focus on planning got the highest average (4.01), with a (high) grade followed by the teacher focus (3.72), The results showed that there are statistically significant differences attributed to the effect of sex in the field of the practice of electronic supervisory practice (3.52), (medium) and finally (3). In favor of males, there are no statistically significant differences attributable to other variables. In light of the results, the study recommended a set of recommendations, the most important of which are: Training workshops for educational supervisors on how to employ computer technologies in educational supervision and benefit from the services provided by the Internet and free sites such as Google Drive and others. In light of the results, a number of recommendations and suggestions were made to improve the quality of technical competencies of educational supervisors in the Eastern Badia and the whole of the Kingdom of Jordan. Including: Increasing training courses with the aim of developing educational supervisors professionally, especially in how to employ active work strategies (investigation, problem solving, critical thinking, and cooperative work), with the aim of increasing their skills in implementing cooperative and group work strategies, employing techniques and technical innovations, and working on the need to employ checks Social communication in order to activate the supervisory process